A General Survey of Song-Poetry (Sanqu) of Yuan China (1260-1368) - Yishan, Zhao (Asian Studies E-Books Online, Collection 2025, 2025)
This book provides a survey of Yuan sanqu , with its principal sections focusing on fundamental theories, compositional features, and historical evolution. Its treatment of qu criticism and bibliography offers a comprehensive perspective on the defining characteristics of sanqu . Serving both as a general overview of sanqu and a foundation for future research, this publication explores this unique yet historically marginalized genre of song-poetry. It generates new insights through textual analysis and the nuanced discussion of dualistic concepts, such as the interplay between literature and music, the Song and Yuan dynasties, and the relationship between ci -lyrics and song-poetry.